2017
DOI: 10.1111/jan.13451
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depressive symptoms among psychiatric nurses who suffered from workplace violence

Abstract: Family support plays the most important role among assaulted psychiatric ward nurses as a protective factor against developing depressive symptoms in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…Resilience is an important factor associated with psychological health in abused PW nurses [36], and resilience can further reduce depressive symptoms [37]. Our results showed that both the BT and SDBT interventions can significantly strengthen abused PW nurses' resilience, as compared to controls, and such results were also found in similar previous studies [22,33].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Resilience is an important factor associated with psychological health in abused PW nurses [36], and resilience can further reduce depressive symptoms [37]. Our results showed that both the BT and SDBT interventions can significantly strengthen abused PW nurses' resilience, as compared to controls, and such results were also found in similar previous studies [22,33].…”
Section: Discussionsupporting
confidence: 87%
“…Depressive symptoms are not uncommon in psychiatric workers [32], and these depressive symptoms are more common among those PW nurses who encounter violence versus those who do not [33]. Abused PW nurses require effective interventions for improving depressive symptoms, and we found that both the BT and SDBT groups had a greater reduction of depressive symptoms than did the control group, with significant difference.…”
Section: Discussionmentioning
confidence: 61%
“…A minimum of 88 respondents was required to achieve a medium effect size with a power of 0.80 at a 5% level of significance (number of predictors = 9). The utilised inputs were similar to those used by previous research on this field .…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, for example, over a 12‐month period 76% of mental health nurses reported depressive symptoms (Hsieh et al . ) and up to 10% of mental health nurses report post‐traumatic stress disorder (Jacobowitz ). The emotional labour of dealing with challenging interpersonal situations with consumers, families, and colleagues can also lead to emotional dissonance (Delgado et al .…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effects of workplace violence and workload demands can contribute to chronic stress and mental distress (Lanctôt & Guay 2014), and lower mental health. In a recent study, for example, over a 12-month period 76% of mental health nurses reported depressive symptoms (Hsieh et al 2017) and up to 10% of mental health nurses report post-traumatic stress disorder (Jacobowitz 2013). The emotional labour of dealing with challenging interpersonal situations with consumers, families, and colleagues can also lead to emotional dissonance (Delgado et al 2017;Edward et al 2017) and substantial levels of burnout (up to 67%; Morse et al 2012).…”
Section: Introductionmentioning
confidence: 99%